South Atlantic Omega Validation. Volume 1. Summary, Analysis, Appendices A-E. - Watt,T M; Bailie,G J; Sutphen,M (1983)
A validation study has been performed of the Omega navigation system in the South Atlantic region. For purposes of the study, the validation region is bounded by 20 deg E and 70 deg W longitude, 20 deg S and 60 deg S latitude, and includes an area of about 35 million square miles. The objectives of the study are to characterize the inherent position-fixing accuracy of the Omega system in the South Atlantic, as it will be when the eight and final transmitting station is commissioned in Australia in 1982, and to validate Omega signal coverage and characteristics in the region. The basic data resources available for meeting these objectives include: (1) Theoretical at 10.2 kHz boundaries of useful signal coverage; (2) A computer-based file of long-term Omega phase-difference data collected by ONSOD at eight fixed monitor sites in the region; (3) Short-term signal amplitude and noise measurements take with both fixed and airborne monitors for ONSOD by the Naval Ocean Systems Center (NOSC) cooperatively with the Federal Aviation Administration Technical Center (FAATC); (4) Shipboard phase, SNR and fix accuracy data from integrated Omega-satellite (IOS) receivers); and (5) Operational signal quality data from the marine and aviation user communities. See also Volume 2, AD-A181 435.